PROVINCIAL GOVERNMENT AUTHORITY ON FOREIGN INVESTMENT COMPANY (STUDY OF PT. EMAS MINERAL MURNI (EMM) NAGAN RAYA DISTRICT, PROVINCE OF ACEH) - Rahmad Maulidin; Sophia Listriani (Fakultas Hukum Universitas Syiah Kuala, 2021)
Abstract PT. EMM is a foreign company engaged in the field of gold mining in the Nagan Raya district, Aceh. The mining business licenses of PT. EMM is invalid because the Central Government does not conduct consultation with the Governor of Aceh as stated under the Government Regulation Number 3 year 2015 and the overlapping of regulation between the Ministerial Decree of Energy and Mineral Resources number 25 year2015 and Act number 11 year 2006 on Aceh Government. This study aims to analyze the meaning of host state control on foreign investment, the implementation of host state control on Act Number 25 year 2007 on Investment and the authority of Aceh government at PT. EMM Nagan Raya district regarding mining license. This research is normative legal research stipulates a systematic exposition by comparing the existing rules and interviewing the mining business licenses foreign company. The outcome shows that the meaning of host state control is the state has rights and responsibility on foreign investment, and the implementation of host state control in Indonesia shows that Indonesia has controlled foreign investment according to Act No.25 year 2007 on investment. Regarding licensing of PT. EMM is the authority of Aceh Government according to Act number 1 year 2006 on the Government of Aceh (UUPA). It is suggested to The Central Government in carrying out its legislation should clarify the rules of authority over foreign investment in the Aceh so that there is no legal overlap between the central government and the Aceh government.Keywords : Host State, Foreign Investment, Authority, Mining License.